The Influence Of Social Support, Work Engagement And Organizational Citizenship Behavior On Work Commitment Of Medical Workers - Kusumowardani; Tirwan; Ilham Arief; Budi Akhmad Tarigan; Joko Ariawan (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
Organizational citizenship behavior is discretionary behavior that plays a role in the psychological and social environment at work. A successful organization or company definitely needs workers who can be responsible and work harder than expected. This can also affect a nurse's professional commitment. This research aims to find out how work involvement and social support influence professional commitment and organizational citizenship behavior with research subjects at general hospitals. This research uses a quantitative approach using purposive sampling techniques to determine the sample size of 100 people. Data was collected using a questionnaire, which was then analyzed using path analysis. The results of this research show that path one, or sub-structural one, namely work involvement and social support, has a significant influence on professional commitment, both simultaneously and partially. Work participation, social support, and professional commitment the outcomes of route or sub-structural two have a major impact on organizational citizenship behavior, partially and simultaneously.